Assessing the impact of transplant site on ovarian tissue transplantation: a single-arm meta-analysis - Baoli Xie; Jiaxu Li; Yingqin Huang; Fu Hang; Qianwen Hu; Jiaxin Yu; Aiping Qin (BMC, 2023)
Abstract Background Survival rates of young women undergoing cancer treatment have substantially improved, with a focus on post-treatment quality of life. Ovarian tissue transplantation (OTT) is a viable option to preserve fertility; however, there is no consensus on the optimal transplantation site. Most studies on OTT are nonrandomized controlled trials with limited sample sizes and uncontrolled statistical analyses, leaving the question of which transplant site yields the highest chance of achieving a live birth unanswered. Objective This meta-analysis aimed to assess the effect of different ovarian transplant sites on postoperative reproductive outcomes. Methods We adhered to the PRISMA Reporting Items for Systematic Reviews and Meta-Analyses recommendations. Systematic searches were conducted in PubMed, Embase, Web of Science, and the Cochrane Library from inception to September 17, 2023. The inclusion criteria were as follows: (1) women who underwent OTT with a desire for future childbirth, and (2) reports of specific transplant sites and corresponding pregnancy outcomes. The exclusion criteria included the inability to isolate or extract relevant outcome data, case reports, non-original or duplicate data, and articles not written in English. Results Twelve studies (201 women) were included in the meta-analysis of cumulative live birth rates (CLBR) after OTT. The CLBR, which encompasses both spontaneous pregnancies and those achieved through assisted reproductive technology (ART) following OTT to the ovarian site, was 21% (95% CI: 6-40, I2: 52.81%, random effect). For transplantation to the pelvic site, the live birth rate was 30% (95% CI: 20-40, I2: 0.00%, fixed effect). Combining transplantation to both the pelvic and ovarian sites resulted in a live birth rate of 23% (95% CI: 11-36, I2: 0.00%, fixed effect). Notably, heterotopic OTT yielded a live birth rate of 3% (95% CI: 0-17, I2: 0.00%, fixed effect). Conclusion Pregnancy outcomes were not significantly different after orthotopic ovarian transplantation, and pregnancy and live birth rates after orthotopic OTT were significantly higher than those after ectopic transplantation. Registration Number INPLASY202390008.